Activating Chalcogen Bonding (ChB) in Alkylseleno/Alkyltelluroacetylenes toward Chalcogen Bonding Directionality Control. (21st October 2020) - Dhaka, Arun; Jeannin, Olivier; Jeon, Ie‐Rang; Aubert, Emmanuel; Espinosa, Enrique; Fourmigué, Marc
Abstract: Activation of a deep electron‐deficient area on chalcogen atoms (Ch=Se, Te) is demonstrated in alkynyl chalcogen derivatives, in the prolongation of the (C≡)C−Ch bond. The solid‐state structures of 1, 4‐bis(methylselenoethynyl)perfluorobenzene (1Se ) show the formation of recurrent chalcogen‐bonded (ChB) motifs. Association of 1Se and the tellurium analogue 1Te with 4, 4′‐bipyridine and with the stronger Lewis base 1, 4‐di(4‐pyridyl)piperazine gives 1:1 co‐crystals with 1D extended structures linked by short and directional ChB interactions, comparable to those observed with the corresponding halogen bond (XB) donor, 1, 4‐bis(iodoethynyl)‐perfluorobenzene. This "alkynyl" approach for chalcogen activation provides the crystal‐engineering community with efficient, and neutral ChB donors for the elaboration of supramolecular 1D (and potentially 2D or 3D) architectures, with a degree of strength and predictability comparable to that of halogen bonding in iodoacetylene derivatives. Abstract : Chalcogen bond activation by alkynyl substitution is realized in bis(selenomethyl‐alkynyl) and bis(telluromethyl‐alkynyl) derivatives, as evidenced in co‐crystals with ditopic Lewis bases, such as 4, 4′‐bipyridine and 1, 4‐di(pyridin‐4‐yl)piperazine, with Te⋅⋅⋅N interactions as short as I⋅⋅⋅N halogen bonds with analogous iodo‐alkynyl derivatives.